Deep learning-based simultaneous registration and unsupervised non-correspondence segmentation of medical images with pathologies - Andresen, Julia; Timo Kepp; Jan Ehrhardt; von der Burchard, Claus; Roider, Johann; Heinz Handels (International Journal of Computer Assisted Radiology and Surgery, 2022)
The registration of medical images often suffers from missing correspondences due to inter-patient variations, pathologies and their progression leading to implausible deformations that cause misregistrations and might eliminate valuable information. Detecting non-corresponding regions simultaneously with the registration process helps generating better deformations and has been investigated thoroughly with classical iterative frameworks but rarely with deep learning-based methods.